A Non-Specific Phytohormone Regulatory Network in Saccharina japonica Coordinates Growth and Environmental Adaptation - Jiexin Cui; Jinli Zhu; Yinru Dai; Jincheng Yuan; Wen Lin; Tao Liu (Plants, 2025)
Saccharina japonica (S. japonica) is a large-scale intertidal aquatic plant that exhibits characteristics such as rhizoid, holdfast, and blade differentiation. It demonstrates remarkable environmental adaptability. However, compared with higher plants, details about its phytohormone content, distribution, synthesis, and accumulation remain poorly understood. In this study, the phytohormone contents distribution and expression patterns of synthetic genes in different parts of S. japonica, including the rhizoid, petiole, basis, middle, and tip, were analyzed in detail by combining targeted metabolomics and transcriptomics analyses. A total of 20 phytohormones were detected in S. japonica, including auxin, abscisic acid (ABA), cytokinin (CTK), ethylene (ETH), gibberellin (GA), jasmonate acid (JA), and salicylic acid (SA), with significant site-differentiated accumulation. ABA and JA were significantly enriched in the tips (28.01 ng·g−1 FW and 170.67 ng·g−1 FW, respectively), whereas SA accumulated specifically only in the rhizoid. We also identified 12 phytohormones, such as gibberellin A1, methyl jasmonate, and trans-zeatin for the first time in S. japonica. Transcriptomic profiling revealed the tissue-specific expression of phytohormone biosynthesis genes, such as CYP735A (CTK synthesis), in the rhizoids and LOX/NCED (JA/ABA synthesis) in the tips. Key pathways, such as carotenoid biosynthesis and cysteine methionine metabolism, were found to be differentially enriched across tissues, aligning with hormone accumulation patterns. Additionally, an enrichment analysis of differentially expressed genes between various parts indicated that different parts of S. japonica performed distinct functions even though it does not have organ differentiation. This study is the first to uncover the distribution characteristics of phytohormones and their synthetic differences in different parts of S. japonica and elucidates how S. japonica achieves functional specialization through non-specific phytohormone regulation despite lacking organ differentiation, which provides an important theoretical basis for research on the developmental biology of macroalgae and their mechanisms of response to adversity.